Inventarisasi dan Karakterisasi Morfologi Tumbuhan Buah Daro di Kecamatan Koto Baru Kabupaten Dharmasraya - Ade Noferta (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2018)
The daro fruit is a plant peculiar to Dharmasraya, until now there is no information about the characteristic of such a plant. The purpose of this research is to invent and to characterize of the morphology of the daro at the District of Koto Baru Regency of Dharmasraya. This research is conducted under both surveys and interview methods then followed with the morphological inventory and characterization. There are found about 103 trees of daros. The descriptive result shows that the tree grows standing upright, woody, and the bark of the tree is rough with light brown and white spotted. The cross-section is round. The leaf is incomplete for it only has a stalk, and a blade of leaf with the dark green upper surface and smooth and light green lower surface, and the leaf spine is fish bone like. Both ends of leaf are conical. The fruit is round and the peel is light brown with dark brown spots. The fruit meat is white and thin. The seeds are dark brown and shiny with 1 cm diameter.